Pharmacokinetics of Enrofloxacin in Plasma, Urine, and Feces of Donkey (Equus asinus) after a Single Intragastric Administration - Bowen Yang; Shijie Liu; Jie Cheng; Honglei Qu; Yanxin Guo; Chuanliang Ji; Yantao Wang; Shancang Zhao; Shimeng Huang; Lihong Zhao; Qiugang Ma (MDPI AG, 2024)
Enrofloxacin is a broad-spectrum antimicrobial agent, but the study of its pharmacokinetics/pharmacodynamics (PKs/PDs) in donkeys is rarely reported. The present study aimed to investigate the pharmacokinetics of enrofloxacin administered intragastrically, and to study the pharmacokinetics of enrofloxacin and its metabolite ciprofloxacin in plasma, urine, and feces, and the PK/PD parameters were investigated to provide a rationale for enrofloxacin treatment in donkeys. A total of five healthy donkeys were selected for intragastric administration of 7.5 mg·kg−1 BW of enrofloxacin by gavage, and blood, urine, and fecal samples were collected. The results showed that the elimination half-life of plasma enrofloxacin was 11.40 ± 6.40 h, Tmax was 0.55 ± 0.12 h, Cmax was 2.46 ± 0.14 mg·L−1, AUC0-∞ was 10.30 ± 3.37 mg·L−1·h, and mean residence time (MRT) was 7.88 ± 1.26 h. The Tmax of plasma ciprofloxacin was 0.52 ± 0.08 h, Cmax was 0.14 ± 0.03 mg·L−1, and AUC0-∞ was 0.24 ± 0.16 mg·L−1·h. Urinary Cmax was 38.18 ± 8.56 mg·L−1 for enrofloxacin and 15.94 ± 4.15 mg·L−1 for ciprofloxacin. The total enrofloxacin and ciprofloxacin recovered amount in urine was 7.09 ± 2.55% of the dose for 144 h after dosing. The total enrofloxacin and ciprofloxacin recovered amount in feces was 25.73 ± 10.34% of the dose for 144 h after dosing. PK/PD parameters were also examined in this study, based on published MICs. In conclusion, 7.5 mg/kg BW of enrofloxacin administered intragastrically to donkeys was rapidly absorbed, widely distributed, and slowly eliminated in their bodies, and was predicted to be effective against bacteria with MICs < 0.25 mg·L−1.